Coccidioidal Meningitis With Hyphal Forms Detected in Cerebrospinal Fluid in a Patient With Ventriculoperitoneal Shunt: A Case Report. (1st December 2021) - Shi, Jeremy; Wong, Myra; Xu, Ya
Coccidioidomycosis is a fungal infection caused by Coccidioides immitis and Coccidioides posadasii . The most severe disseminated coccidioidomycosis results in meningoencephalitis. Literature review reveals very rare reports of hyphal forms of coccidioides organisms detected in CSF. We present a case of a 58-year-old Hispanic male with a 10-year persistence of CM and many ventriculoperitoneal shunt reversions. The patient initially presented with a hydrocephalus of unknown source. The diagnosis of CM was made three years later based on a culture. On this presentation at the emergency department (ED), the patient reported one day of worsening left-sided weakness, altered mental status, and vomiting. We detected the hyphal forms of coccidioides in the cerebrospinal fluid (CSF) during cytopathology examination. Awareness of this reversion from spherule form to hyphal form is helpful in diagnosis and treatment. The hyphal forms of coccidioides may be associated with the increased risk of obstruction of the shunts. It is important to submit CSF for cytopathology examination for diagnosis, especially in patients with shunts.